Spray pyrolysis developed Nd doped Co3O4 nanostructured thin films and their structural, and opto-nonlinear properties for optoelectronics applications. (June 2022) - Shkir, Mohd.; Khan, Aslam; Imran, Mohd; Ajmal Khan, M.; Zargar, Rayees Ahmad; Alshahrani, Thamraa; Deva Arun Kumar, K.; Mohanraj, P.; Chandekar, Kamlesh V.; AlFaify, S.
Graphical abstract: Highlights: Novel pure and Nd doped Co3 O4 films were developed by cost-effective spray pyrolysis route. XRD/Raman/EDX/SEM e-mapping studies approves the monophasic Nd:Co3 O4 films fabrication. Enhancement in photoluminescence emission intensity was observed and discussed. The χ 3 values are found between 4 × 10 -13 to 1.27 × 10 -10 esu for Nd doped Co3 O4 films. Nonlinear refractive index (n2 ) are found between 5.86 and 1.35(×10 -9 ) esu., for Nd:Co3 O4. Abstract: Herein we are reporting the facile spray pyrolysis fabrication of different Neodymium (Nd) contents loaded cobalt oxide (Co3 O4 ) nanostructured thin films at 400 °C substrate temperature and investigated for opto-nonlinear applications. Structural and vibrational studies approve the cubic system of all films with the low crystallite size between 25 and 20 nm. FESEM e-mapping and EDX analyses further confirm the homogeneous Nd doping in Co3 O4 films. FESEM study reveals that the grains are very fine and distributed throughout the films. The optical study reveals that the grown films possess two energy gaps which are between 2.03 and 2.15 eV and 1.49–1.55 eV. Photoluminescence study has been performed at three different excitation wavelengths and the mono-emission was noticed at 375, 500 and 754 nm. Furthermore, the linear absorption and refractive indices were determined along with dielectric and electrical properties. Also, the nonlinear susceptibility and refractive index were determined and found to be in range of 4 × 10 -13 to 1.27 × 10 -10 esu and 5.86 × 10 -12 to 1.35 × 10 -9 esu., respectively.